Aspek Penerapan Protokol Routing Directed Diffusion Pada WSN Untuk Deteksi Kebakaran - Novri Meirizal; Indra Yasri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The forest fire disaster a few years back became be a national disaster even at certain times is already reaching out to the country's neighbors. One of the technologies that are used to anticipate forest fires is use Wireless Sensor Network (WSN). Some research related to the anticipation of WSN fires have been used, but still are testing approach and not using a Routing protocols. Research that uses the Routing protocol still using level simulation. On this research will implement Routing protocols in this regard which Directed diffusion Routing protocol (DD). Implementation begins with a gather existing scenarios in the field of data then this scenario will be modeled on c++ programming languages in accordance with the existing features in DD Routing protocol. The scenario that will be modeled include the number of Sensor nodes involved in accordance with their respective role as outlined in the following: the Coordinator will forward the message in accordance with the interest requested by user interest messages sent in the form of broadcast to all nodes that are connected in the Network up towards the node that is closest to the target. Next the node that receives the message of interest will give a response to the Coordinator. Then the Coordinator will establish a communication Network path will be dilaui by the message sender node of the target. From some alternative paths available Coordinator will be finalised the most optimal routes. After the model of the Routing protocols are ready on the Arduino Uno next done testing with Network install using nRF24L01 module. Trial results show the path that is specified by the node parameter obtained efficiency Coordinator for communication in the form of delay and throughput that is considered the most optimal.Keyword : Wireless Sensor Network, nRF24L01, Arduino, Directed diffusion, DHT11, Arduino IDE.